Effect of Leu-Enkephalin (Dalargin) on Apoptosis and Necrosis of Leukocytes After Cold Stress - Moisieieva, Nataliia; Gulevskyy, Oleksandr; Gorina, Olga (Problems of Cryobiology and Cryomedicine, 2022)
The effect of synthetic leu-enkephalin (dalargin) on apoptosis and necrosis in leukocytes after cold stress on the morphological characteristics of cells and using fluorescent dyes Hoechst 33342 as well as propidium iodide was studied. The degree of cold stress influence depending on the duration of incubation of cell suspension at 0–2 and 37°C on the initiation of apoptosis and necrosis on the morphological characteristics of cells was determined. It has been proven that the ratio of apoptotic cells to necrotic ones was maximal after the use of the regimen as follows: preliminary incubation of leukocytes at 37°C – 15 min, cell exposure at 0–2°C – 15 min and subsequent incubation of leukocytes at 37°C. It has been confirmed that pre-incubation of cells with neuropeptide to cold stress affects the effectiveness of the protective action of dalargin, in particular, contributes to a significant (p ≤ 0.05) reduction in the percentage of leukocytes with morphological signs of apoptosis and necrosis. It was found that a consistent increase in temperature after cold stress to 37°C did not affect the percentage of cells with morphological signs of apoptosis and necrosis. It has been validated that the percentage of leukocytes with the apoptosis and necrosis signs after cold stress was significantly reduced after incubation of leukocytes with dalargin at a concentration of 10–9 mol/l. Probl Cryobiol Cryomed 2022; 32(1): 014–023